2017
DOI: 10.1111/jam.13430
|View full text |Cite
|
Sign up to set email alerts
|

Limited effectiveness of over-the-counter plant preparations used for the treatment of urinary tract infections as inhibitors of the urease activity fromStaphylococcus saprophyticus

Abstract: While over-the-counter plant preparations may be considered an alternative to traditional antibiotics for the treatment of UTIs, they should be used with caution and a product should be matched to the properties of the virulence factors of the bacterial pathogen involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Urease activity measurements in fresh feces were measured within 2 days using the indophenol blue colorimetry method described previously ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Urease activity measurements in fresh feces were measured within 2 days using the indophenol blue colorimetry method described previously ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current percentage of approved antibacterial compounds from medicinal plants does not accurately reflect the potential of these compounds for future applications as antimicrobial therapies. Indeed, there are some inherent challenges regarding the use of plant natural extracts as antimicrobial pharmaceuticals: Recent studies have shown that medicinal plant compounds should be used with caution in the absence of accurate evidence of their effectiveness [ 189 ]. Well-controlled, double-blind toxicological and clinical studies to prove their efficacy and safety are rare [ 190 ].…”
Section: Challenges Surrounding Medicinal Plant Antimicrobial Activitymentioning
confidence: 99%
“…In previous studies, we grew S. saprophyticus in an artificial urine medium and tested the effects of various compounds on the increase in pH that can occur as a result of urease activity. We found that some chemical inhibitors such as fluorofamide and acetohydroxamic acid and some over‐the‐counter products such as green tea extract could delay the increase in pH; however, others such as catechin had no effect (Loes et al ; Deutch ). S. saprophyticus was grown in an artificial urine medium without or with 10% (v/v) DMSO.…”
Section: Resultsmentioning
confidence: 98%
“…These preparations contain inhibitors with diverse chemical structures (Modolo et al ; Hassan and Zemlička ), which have been incorporated into several commercial products (Albrecht et al ; Naber ). Some caution is necessary in using these products, however, because the urease from S. saprophyticus does not contain cysteine and is insensitive to many inhibitory compounds (Schäfer and Kaltwasser ; Jose et al ; Kuroda et al ; Loes et al ; Deutch ).…”
Section: Introductionmentioning
confidence: 99%